The Abscopal Effect in the Era of Checkpoint Inhibitors - Kodet, Ondřej; Němejcova, Kristýna; Strnadová, Karolína; Havlínová, Andrea; Dundr, Pavel; Krajsová, Ivana; Štork, Jiří; Smetana, Karel; Lacina, Lukáš (International journal of molecular sciences, 2021)
Therapy targeting immune checkpoints represents an integral part of the treatment for patients suffering from advanced melanoma. However, the mechanisms of resistance are responsible for a lower therapeutic outcome than expected. Concerning melanoma, insufficient stimulation of the immune system by tumour neoantigens is a likely explanation. As shown previously, radiotherapy is a known option for increasing the production of tumour neoantigens and their release into the microenvironment. Consequently, neoantigens could be recognized by antigen presenting cells (APCs) and subjected to effector T lymphocytes. Enhancing the immune reaction can trigger the therapeutic response also at distant metastases, a phenomenon known as an abscopal effect (from "ab scopus", that is, away from the target). To illustrate this, we present the case of a 78-year old male treated by anti-CTLA-4/ipilimumab for metastatic melanoma. The patient received the standard four doses of ipilimumab administered every three weeks. However, the control CT scans detected disease progression in the form of axillary lymph nodes metastasis and liver metastasis two months after ipilimumab. At this stage, palliative cryotherapy of the skin metastases was initiated to alleviate the tumour burden. Surprisingly, the effect of cryotherapy was also observed in untreated metastases and deep subcutaneous metastases on the back. Moreover, we observed the disease remission of axillary lymph nodes and liver metastasis two months after the cryotherapy. The rarity of the abscopal effect suggests that even primed anti-tumour CD8+ T cells cannot overcome the tumour microenvironment's suppressive effect and execute immune clearance. However, the biological mechanism underlying this phenomenon is yet to be elucidated. The elicitation of a systemic response by cryotherapy with documented abscopal effect was rarely reported, although the immune response induction is presumably similar to a radiotherapy-induced one. The report is a combination case study and review of the abscopal effect in melanoma treated with checkpoint inhibitors.
Keywords: výsledek terapie; nádorové mikroprostředí; Models, Immunological; Male; Immune Checkpoint Inhibitors; anti-CTLA-4; modely imunologické; kryoterapie; Skin Neoplasms; ipilimumab; antigeny nádorové; Aged; mužské pohlaví; senioři; paliativní péče; Antigen-Presenting Cells; Palliative Care; Treatment Outcome; Melanoma; tumor neoantigens; antigen prezentující buňky; Ipilimumab; lidé; Humans; melanoma; Antigens, Neoplasm; abscopal effect; inhibitory kontrolních bodů; wound healing; nádory kůže; Cryotherapy; cryotherapy; Tumor Microenvironment; melanom